A management strategy for the long-term conservation of the Endangered sand-dune lizard Liolaemus multimaculatus in the Pampean coastal dunes of Argentina. Issue 3 (11th August 2017) - Kacoliris, Federico P.; Velasco, Melina A.; Kass, Camila; Kass, Nicolas; Simoy, Verónica; Grilli, Pablo G.; Martínez Aguirre, Tomas; Di Pietro, Diego O.; Williams, Jorge D.; Berkunsky, Igor
Abstract: The sand-dune lizard Liolaemus multimaculatus is an Endangered species endemic to the Pampean coastal dunes of Argentina. To inform the development of a future Action Plan for this species, we investigated the demography and conservation status of all remaining populations, and we suggest management actions appropriate to local needs. We used population viability analysis to assess extinction risk in three inbreeding scenarios and estimate the minimum viable population and the minimum area requirement. To assess the current status of each local population, we used information related to population size, human pressure and connectivity. The results were then used to set and prioritize conservation management actions at local level. Our models indicated that populations of > 2, 400 individuals would be viable in the long term and that inbreeding depression has a strong effect on extinction risk. The southern patches of coastal dune contain the largest populations of sand-dune lizards, and they are also better connected and less threatened. We suggest land protection as the priority management action for populations larger than the minimum viable population, whereas habitat recovery, when possible, should be the priority for patches of coastal dune smaller than the minimum area requirement. Supplementation with a small number of individuals could stabilize unviable populations but should be considered only in certain situations. The long-term conservation of the sand-dune lizard will be feasible only if a conservation action plan is developed and implemented.